Γ‐Octalactone, an effective oviposition stimulant of Bactrocera tryoni. (23rd October 2019) - Kempraj, Vivek; Jean Park, Soo; Taylor, Phillip W.
Abstract: Insects commonly rely on olfactory, gustatory and visual cues when deciding where to lay eggs. The olfactory cues that stimulate oviposition in the Queensland fruit fly, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), are not well understood. Here, we show that two known oviposition stimulants of the Oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae)—γ‐octalactone and benzothiazole—strongly elicit aggregation and oviposition in B. tryoni . Two other known oviposition stimulants of B. dorsalis —ethyl tiglate and 1‐octen‐3‐ol—elicit aggregation but not oviposition. Highlighting species overlap, but also differences, in oviposition stimulants, these findings have practical application for mass‐rearing in which vast numbers of flies are reared for sterile insect technique programs and may also have practical application in the development of pest management and monitoring tools.